Has gender any effect on the relationship between time limit at VO2max velocity and swimming economy? - Fernandes, R. J.; Billat, V. L.; Cruz, A. C.; Colaco, P. J.; Cardoso, C. S.; Vilas-Boas, J. P. (Journal of Human Movement Studies, 2005)
The purpose of this study was to examine the effect of gender on the relationship between time limit at the minimum velocity that elicits maximal oxygen consumption (TLim-vVO2max) and three swimming economy (SE) related parameters: the energy cost corresponding to vVO2max (CvVO2max), the slope of the regression line obtained from the relationship between energy expenditure (E) and corresponding velocities in a incremental test (Cslope) and the ratio obtained by the mean E value and the velocity mean value of the incremental test (Cinc). Each subject of two gender groups-11 male and 12 female swimmers-performed an incremental test for vVO2max assessment and an all-out TLim-vVO2max test. TLim-vVO2max, vVO2max, CvVO2max, Cslope and Cinc averaged, respectively, 244.6±56.5s, 1.45±0.04m/s, 15.9±2.2J.kg-1m-1, 35.0±4.8J.kg-1m-1 and 14.3±2.4J.kg-1m-1 in the male group and 248.0±60.5s, 1.33±0.04m/s, l 4.3±1.81J.kg-1m-1, 35.7±6.4J.kg-1m-1 and 11.5±1.5J.kg-1m-1 in the female group. An inverse correlation was found between TLim-vVO2 max and Cslope for the entire group (r=-0.78, p<.001) and for each gender group (r=-0.90, p<.001 and r=-0.61, p<.05, for female and male respectively), confirming that SE is a very important performance influencing factor. Complementarily, despite the relationship between energy cost and TLim-vVO2max efforts is evident in each gender, the TLim-vVO2max tests performed by the female swimmers seem to depend more on their own SE than on male swimmers.